Triage for conserving populations of threatened species: The case of woodland caribou in Alberta. - Hauer, G.; Adarnowicz, W.; Boutin, S.; Schneider, R. (2010)
Prioritization of conservation efforts for threatened and endangered species has tended to focus on factors measuring the risk of extirpation rather than the probability of success and cost. Approaches such as triage are advisable when three main conditions are present: insufficient capacity exists to adequately treat all patients, patients are in a critical state and cannot wait until additional capacity becomes available, and patients differ in their likely outcome and/or the amount of treatment they require. The objective of our study was to document the status of woodland caribou (Rangifer tarandus) herds in Alberta, Canada, with respect to these three conditions and to determine whether a triage approach might be warranted. To do this we modeled three types of recovery effort – protection, habitat restoration, and wolf control – and estimated the opportunity cost of recovery for each herd. We also assessed herds with respect to a suite of factors linked to long-term viability. We found that all but three herds will decline to critical levels (<10 animals) within approximately 30 years if current population trends continue. The opportunity cost of protecting all ranges by excluding new development, in terms of the net present value of petroleum and forestry resources, was estimated to be in excess of 100 billion dollars (assuming no substitution of activity outside of the ranges). A habitat restoration program applied to all ranges would cost several hundred million dollars, and a provincial-scale wolf control program would cost tens of millions of dollars. Recovery costs among herds varied by an order of magnitude. Herds also varied substantially in terms of their potential viability. These findings suggest that woodland caribou in Alberta meet the conditions whereby triage should be considered as an appropriate conservation strategy.